Epigenomics of complex disease - Petronis, Art (Henry Stewart Talks, 2010)
Complex disease, Non-mendelian features, Epigenetic heritability, Partial epigenetic stability, Inherited and acquired epigenetic misregulation of genes and genomes, Microarrays and epigenomic profiles in health and disease